Firstly, we rearrange the equation so that there will only be equation with one unknown on one side while integer on the other side.
So,
x^(4/3)+9=25x43+9=25
x^(4/3)=25-9x43=25−9
x^(4/3)=16x43=16
To eliminate the power on unknown xx, we need to whether add to the power of or to the power root of on both side of the equation. For example;
x^(4/3)=16x43=16 also equals to root(3)(x)^(4)=163√x4=16
Let say we want to eliminate the power root of 33 on xx, we must add to the power of 33 onto both side of equation;
x^(4/3)=16x43=16
Add to the power of 33 on both side of equation;
x^((4/3)(3))=16^3x(43)(3)=163
x^(4)=4096x4=4096
Let say then we want to eliminate the power of 44 on xx, we must add to the power root of 44 onto both side of equation;
x^(4)=4096x4=4096
Add to the power root of 44 on both side of equation;
x^((4)(1/4))=4096^(1/4)x(4)(14)=409614
x=8x=8